Comparation Tidal Harmonic Based on IoT Instrument Using Admiralty Method in Tanjungpinang Waters - Alajuri, M Hasbi Sidqi; Kusuma, Hollanda Arief; Suhendra, Tonny; Setyono, Dwi Eny Djoko (Politeknik Negeri Batam, 2024)
Tides are the rising and falling movement of sea level caused by the gravitational force of celestial bodies such as the moon and sun on the mass of seawater on earth. The aim of this research is to compare the use of time series of harmonic constant parameters obtained from tidal data stored in the tool using the admiralty method. Research activities were carried out at the international port of Dompak Island, Tanjungpinang City, Riau Islands. This tidal data is analyzed by admiralty. This method is used to analyze harmonic constants and identify patterns and sea level levels. Based on the results obtained, the type of tide in Tanjungpinang waters is a mixed tide (single dominant) with an F value of 2.01 to 2.07. The sea level elevation values